2020
DOI: 10.1002/anie.202003058
|View full text |Cite
|
Sign up to set email alerts
|

The Length of a Ubiquitin Chain: A General Factor for Selective Recognition by Ubiquitin‐Binding Proteins

Abstract: The attachment of ubiquitin (Ub) chains of various length to proteins is a prevalent posttranslational modification in eukaryotes. The fate of a modified protein is determined by Ub‐binding proteins (UBPs), which interact with Ub chains in a linkage‐selective manner. However, the impact and functional consequences of chain length on the binding selectivity of UBPs remain mostly elusive. We have generated Ub chains of defined length and linkage by using click chemistry and GELFrEE fractionation. These defined p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…With sufficient amounts of non-hydrolyzable site-specifically ubiquitylated H1 in hand, we set out to dissect the ubiquitylation-dependent modular interactome. Building on previous efforts 53 , 54 , we adapted an affinity purification-mass spectrometry (AP-MS) based approach to identify Ub-dependent interaction partners of H1 using its N-terminal Strep-tag II for enrichment (Fig. 2a , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With sufficient amounts of non-hydrolyzable site-specifically ubiquitylated H1 in hand, we set out to dissect the ubiquitylation-dependent modular interactome. Building on previous efforts 53 , 54 , we adapted an affinity purification-mass spectrometry (AP-MS) based approach to identify Ub-dependent interaction partners of H1 using its N-terminal Strep-tag II for enrichment (Fig. 2a , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…dimers/tetramers) rather interacted with enzymes involved in protein modification (e.g. kinases, proteases, and also E3 ligases) ( 170 ). In line with this, previous studies already demonstrated that different deubiquitinating enzymes are influenced by different chain lengths.…”
Section: Drawing Parallels To the Ubiquitin Systemmentioning
confidence: 99%
“…The authors also used gel eluted liquid fraction entrapment electrophoresis to separate the Ubs into Ub 2, Ub 4 , Ub 6+ to examine their interactors separately. 39 Signicant differences were observed in the interactors of Ubs with different lengths. For example, Ub-associated domaincontaining protein 1 (Ubac1), RING nger 123 (RNF123), and USP15 only interact with long Ub chains (Ub 4 , Ub 6+ ).…”
Section: This Journal Is © the Royal Society Of Chemistry 2020mentioning
confidence: 99%
“…Such probes usually contain one or more Ub units and an enrichment/purication tag. [33][34][35][36][37][38][39][40] Ub units can be either natural or mimetics that do not impact the interaction with linkage-specic interactors ( Fig. 4a).…”
Section: Probes Capturing Ub Interactorsmentioning
confidence: 99%
See 1 more Smart Citation